Modeling Quality and Pollution Load Capacity of the Musi River Using QUAL2Kw - Rafles Ami Poza; Nur Faizaturrohmah; Erlina Kurnianingtyas; Isoralla; Dion Awfa; Rifka Noor Azizah; Muhammad Ulin Nuha; Arif Rohman; Aulia Try Atmojo; Daffa Adli Nauval Purnomo (LPPMP Universitas Bhayangkara Jakarta Raya, 2026)
The aim is to analyze water quality and determine the pollutant load of the Musi River in Palembang City using the QUAL2K model. The method involved collecting water-quality data (TSS, NH₃, COD, and pH), calibrating and validating the model using hydraulic and water-quality parameters, and simulating the burden on the power capacity of the polluted river. The research results show that the QUAL2Kw model has high accuracy and performs well under representative field conditions. As for the spatial distribution, TSS and NH3 concentrations tend to increase from upstream to downstream due to anthropogenic activity, but they remain within safe limits. For COD, conditions tend to exceed the river’s capacity, with marked negative values. This indicates a high organic pollution pressure and the potential to degrade the quality of the aquatic ecosystems. This model can be used as a good basis for sustainable management of river water quality.